Annotated record of the detailed examination of Mn deposits from DSDP Leg 34 (Holes 319, 319A, 320, 320B, 321) - Yeats, Robert S; Hart, Stanley R (Supplement to: Vallier, Tracy L; Salisbury, Matthew H; Sachs, H; Quilty, Patrick G; Hart, Roger A; Benson, William E; Bass, Manuel N; Ade-Hall, James M; Yeats, Robert S; Hart, Stanley R (1976): Initial Reports of the Deep Sea Drilling Project. Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, XXXIV, 814 pp, https://doi.org/10.2973/dsdp.proc.34.1976, 1976)
The Bauer Deep is the depression between the active East Pacific Rise on the west and the extinct Galapagos Rise on the east. The selection of Site 319 was based on a detailed survey of the Bauer Basin during Yaloc-13, Leg 3. Leg 3. It is in a basin about 8 km wide (east-west) at 13°OO.8'S, which is part of a broadly faulted zone on the low western flank of the Galapagos Rise. Site 320 and 321 where located in order to survey the Nazca plate. The objectives for Site 320 were (1) to core basalt continuously as deep as possible, with one and possibly two re-entries; (2) to determine the history of the eastern Nazca plate for the last 30 to 40 m.y., (3) to determine the effectiveness of the Peru-Chile Trench as a barrier to turbidity current dispersal. Site 321 is located on the eastern edge of the Nazca plate immediately south of the Mendafia Fracture Zone. The objectives for Site 321 were similar as those for Site 320.